Epidemiology and Public Health Considerations of Hookworm Infection - Alanzi, Sarah Saab; Fahad Ibrahim Alrubyea,; Dakheel Maashi D Alshammari,; Saeed Meshal Alzahrani,; Abdullah Hamed Mohammed Almatrafi,; Nasser Amer Al-Otaibi,; Raed Abdullah Alzmea,; Waleed Mahdi Hussein Hakami,; Khalid Awadh K Alrowili,; Khalid Mohammed Albassam, (Saudi Journal of Medicine and Public Health, 2025)
Background: Hookworm infection remains a major neglected tropical disease, particularly in lowincome tropical and subtropical regions. Caused mainly by Ancylostoma duodenale and Necator americanus, it contributes significantly to irondeficiency anemia, malnutrition, and impaired physical and cognitive development, especially among children and pregnant women. Aim: This article aims to review the epidemiology, pathophysiology, clinical manifestations, evaluation, and management of hookworm infection, emphasizing public health implications and preventive strategies. Methods: A narrative review approach was employed, synthesizing current clinical, epidemiological, and public health evidence related to hookworm infection, including diagnostic methods, pharmacologic treatments, and preventive interventions. Results: Globally, hookworm infects approximately 470 million individuals, with disease burden closely linked to poverty, poor sanitation, and barefoot soil exposure. Chronic intestinal blood loss leads to anemia and protein malnutrition. Diagnosis primarily relies on stool microscopy, supported by eosinophilia and epidemiological risk factors. Albendazole remains the most effective treatment, though reinfection is common. Integrated strategies combining deworming, nutritional support, sanitation, and health education are essential. Conclusion: Hookworm infection continues to pose substantial clinical and public health challenges. Sustainable control requires coordinated medical, preventive, and socioeconomic interventions.